Ildsjeler og ildsteder: En etnografisk studie av ledelsesdynamikker i vitale ungdomsarbeid i Den norske kirke - Hallesby Norheim, Bård Eirik; Tveitereid, Knut (Tidsskrift for Praktisk Teologi, 2020)
No particular vocation is formally assigned to running local youth ministry in the Church of Norway. Despite the fact that no one has to do youth ministry, many local youth ministries in the Church of Norway are thriving. This article draws on fieldwork, data and analysis of a three-year long research project (2016-2019) which sought to describe and understand how various patterns of dynamics in leadership emerge in vital youth ministries. In the data we singled out four independent – yet intertwined – dynamic patterns of leadership: a culture of enthusiasts, a practice of welcome, a hierarchy of development and responsibility, and finally an understanding of theology as approximate. These patterns create an interplay between the centripetal dynamics of an attracting place (No.: «ildsteder» / Eng.: «fire places») and centrifugal dynamics ofchange and moving on (No.: «ildsjeler» / Eng.: «fire starters»).